PENGELOLAAN UANG SAKU SANTRI MADRASAH ALIYAH PONDOK PESANTREN DARUNNAIM PUTRI PONTIANAK - Hasdianty, Zafitiya Anisha; Basri, Muhammad; Kuswanti, Heni (Universitas Tanjungpura, 2025)
Entering the era of globalization, many impacts occur on an individual's financial behavior in order to meet basic needs as well as unlimited desires, one of which is the santri. This research aims to understand how pocket money management is carried out by the students of Madrasah Aliyah Pondok Pesantren Darunnaim Putri. This research uses a quantitative approach in the form of path analysis. (Path Analysis). The number of respondents in this study uses three levels, namely grades X, XI, and XII for the academic year 2023/2024. The sample in this study consists of 110 students. Data was collected from the distributed questionnaire. The technique for analyzing data is using descriptive analysis. Based on the research findings, it is stated that: (1) Economic education within the family has a direct and significant impact on the management of pocket money, evidenced by the t-value (2.445) the table value (1.982) with a significance level of 0.016 0.05; (2) Financial literacy has a direct and significant impact on the management of pocket money, evidenced by the t-value (5.473) the table value (0.187) with a significance level of 0.000 0.05; (3) Economic education within the family does not have a direct impact on financial literacy, evidenced by the t-value (0.419) the table value (1.982) with a significance level of 0.676 0.05.